THU0268 Prevalence and features of celiac disease in patients with systemic autoimmune diseases: results of a large multicenter study. (15th June 2017) - Bartoloni, E; Alunno, A; Bistoni, O; Cavagna, L; Nalotto, L; Baldini, C; Priori, R; Picarelli, G; Fischetti, C; Franceschini, F; Quartuccio, L; Carubbi, F; et al.
Abstract : Background: Celiac disease (CD) is an inflammatory and immune-mediated gluten-dependent enteropathy occurring in genetically susceptible individuals. CD is recognized to affect between 0.6% and 1% of worldwide population, with wide regional differences. Disease clinical features are protean and highlight the systemic nature of the disease. In recent years, an increased prevalence of CD has been also reported in patients with connective tissue diseases (CTDs). This association may be due to a shared genetic predisposition, to immunological mechanisms and/or exposure to a common triggering event. However, this observation remains controversial since data are usually based on descriptive case reports. Different methods of antibody detection and enrolled population sample size may contribute to result discordance. Moreover, CD diagnosis is often delayed because disease clinical spectrum may be atypical mimicking rheumatologic conditions and autoimmune disease itself may display typical symptoms of CD. Undoubtedly, awareness of CD occurrence in CTDs is important to prevent potential long-term systemic complications related to an unrecognized CD in these patients. Objectives: To evaluate the prevalence of overt and subclinical CD and features of the disease in a large cohort of patients with systemic lupus erythematosus (SLE), systemic sclerosis (SSc) and primary Sjögren's syndrome (pSS) with a multicenter prospective study involving 9 Italian Rheumatology Units. Methods: Data from consecutive 580 SLE, 354 pSS and 524 SSc patients were collected. Disease-specific features were registered in patients with known CD. Remaining patients were tested for IgA transglutaminase (Eu-tTG® human IgA new, Eurospital S.p.A., Trieste). Anti-endomysium (EMA) IgA and IgG were tested in IgA tTG positive and borderline patients. Esophagogastroduodenoscopy with duodenal biopsy was proposed in IgA tTG+/EMA+, IgA tTG-/EMA+ and IgA tTG±/EMA+ patients. Results: CD prevalence was 1, 7% in SLE, 7% in pSS and 1, 3% in SSc patients. Higher frequency of elevated liver enzymes was detected in SLE-CD and of herpetiform dermatitis in SSc-CD patients in comparison to the other groups (p<0.05 for both). Interestingly, pSS-CD and SSc-CD patients were younger and had a lower age at diagnosis in comparison to pSS and SSc without CD (p<0.05 for all). Of interest, higher prevalence of CD was detected in SSc patients with diffuse form in comparison to limited SSc (86% vs 14%, p=0.002). Conclusions: The results of the present large multicenter study confirm higher prevalence of CD in CTD patients, especially in pSS. Screening of CD may be considered in younger patients with CTD and lower age at diagnosis. The strong association of CD with the diffuse type of SSc is of note and suggests that different, still unexplored, pathogenic mechanisms may characterize the two subsets of the disease. Disclosure of Interest: None declared